2022
DOI: 10.1002/ajim.23340
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and suicidal ideation among male construction workers in the United States

Abstract: Background: Male workers in the US construction industry have a higher suicide rate than other workers in the nation. However, related research on this population remains sparse. This study evaluated psychological distress and suicidal ideation in these workers, and possible underlying factors. Methods: Data from the National Survey of Drug Use and Health from 2008 to 2014 were analyzed. Stratified and multiple logistic regression analyses were conducted to examine factors associated with psychological distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…Moreover, male CIWs in Ireland had higher prevalence rates compared to a number of other population groups. For example, SI rates were higher among male CIWs in Ireland compared to those reported for CIWs in previous studies over similar time periods of twelve months (25) and two weeks when using item nine of the PHQ-9 as the primary outcome measure for SI (26). While there is no comparable data for NSSI or SA among CIWs in the wider literature, our ndings indicate that the lifetime prevalence rate for NSSI is consistent with international data (44) but the lifetime SA rate among male CIWs in Ireland is considerable higher (21).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Moreover, male CIWs in Ireland had higher prevalence rates compared to a number of other population groups. For example, SI rates were higher among male CIWs in Ireland compared to those reported for CIWs in previous studies over similar time periods of twelve months (25) and two weeks when using item nine of the PHQ-9 as the primary outcome measure for SI (26). While there is no comparable data for NSSI or SA among CIWs in the wider literature, our ndings indicate that the lifetime prevalence rate for NSSI is consistent with international data (44) but the lifetime SA rate among male CIWs in Ireland is considerable higher (21).…”
Section: Discussionmentioning
confidence: 74%
“…There is a dearth of research exploring the prevalence and associated factors of SI, NSSI and SA among male CIWs. Three studies have explored SI among CIWs and reported prevalence rates of between 2.5% − 12% (25,26). An additional study on SI among construction industry apprentices reported a twelvemonth prevalence rate of 29.4% (27).…”
Section: Introductionmentioning
confidence: 99%
“…The study aims to ascertain whether FI aggravates SI through EE and ROE by adopting conservation of resources (COR) (Hobfoll, 1989) and interpersonal theory of suicide (IPTS) (Orden et al, 2010). This study implies that FI spills over to the workplace and aggravates EE (Lim and Tai, 2014), enhancing the urge to SI (Dong et al, 2022). As per IPTS (Orden et al, 2010), professionals who are the victims of FI and experience EE are deprived of belongingness needs.…”
Section: Present Studymentioning
confidence: 99%
“…7 Research at the national and international levels have indicated specific industries may be more vulnerable to suicide or suicide ideation, including first responders, 8 agriculture, 9 and construction. 10 In addition to the psychological impact on the employees, families, and communities of the person who died by suicide, workplace suicides incur a significant economic cost due to medical, legal, and lost earnings due to premature mortality. 11,12 In North Carolina (NC), prior studies that have investigated fatal occupational injuries have often focused on deaths due to homicide and unintentional injury, but did not report on the incidence of suicides at work.…”
Section: Introductionmentioning
confidence: 99%
“…The number of workplace fatalities by suicide reached the highest level on record in 2019 (the most recent year for which data are available) 7 . Research at the national and international levels have indicated specific industries may be more vulnerable to suicide or suicide ideation, including first responders, 8 agriculture, 9 and construction 10 . In addition to the psychological impact on the employees, families, and communities of the person who died by suicide, workplace suicides incur a significant economic cost due to medical, legal, and lost earnings due to premature mortality 11,12 …”
Section: Introductionmentioning
confidence: 99%